The role of toxoplasma, rubella, cytomegalo virus, herpes virus infection as a risk factor for sensory hearing loss in children - Bambang Udji Djoko Rianto; Veby Novri Yendri; Gesit Purnama Giana Deta (Indonesian Journal of Biomedicine and Clinical Sciences, 2024)
Toxoplasma, rubella, cytomegalovirus and herpes virus infection (TORCH) are syndromes that are considered risk factors for deafness.. This study aims to prove the risk factors which play the most significant role in the incidence of Sensory Hearing Loss in children. This used a case-control design, conducted at JIH Yogyakarta Hospital started from December 2023 to June 2024. All participants aged less than 5 years underwent oto-acoustic emission (OAE) examination, then determined presence or absence toxoplasma, rubella, cytomegalovirus and herpes virus using the electrochemiluminescence immunoassay (ECLIA) method. The inclusion criteria for the case group were: 1) patients diagnosed with sensory hearing loss (SHL), while the control group was normal. The exclusion criteria for the case and control groups there were non-infectious risk factors. Based on a type I error of 5% and type II error of 20%. The recommended sample size is 18 samples per group. Statistical analysis used stratified statistical analysis. The results of this study show that the combination of rubella + CMV had the greatest odds ratio (OR: 8) of sensory hearing loss, CMV OR: 0.62, herpes simplex virus OR: 0.28, combination of rubella + herpes simplex virus OR: 0.28, toxoplasma + CMV OR: 0.28, rubella obtained OR: 1 .5, and the combination of rubella + CMV + herpes simplex virus OR: 0.1. Based on these results the combination of rubella + CMV had the greatest OR compared to the combination of other risk factors and single risk factor.